Infographic on global leaders - Kelan, Elisabeth (Cranfield University, 2016)
Infographic from an extensive research project on how men as middle managers can engage in gender inclusive leadership.
Keywords: 'gender'; 'inclusivity'; 'gender equality'; 'inclusion'; 'men'; 'diversity'; 'leadership'; 'Organisation and Management Theory'; 'Business and Management not elsewhere classified'